MINANGKABAU ADOLESCENT PARENTING STYLES AND THE RISK OF SUBSTANCE USE - Fernanda, Yogi; Fransiska, Mellia; Alhamda, Syukra (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Bukittinggi has a significant increase in drug abuse, from 67 cases in 2022 to 100 cases in 2023 (33%). One of the factors that effect to drug abuse among adolescent was the parenting style. This study aims to determine the relationship between parenting and the risk of drug abuse and analyse the parenting style of adolescent drug abuser. This study was a Mix Method research on the Explanatory Sequential Design model. The quantitative research involved 143 Minangkabau adolescents and the informants are addiction counselors, community leaders, drug abuser and parents. Quantitative data was collected using questionnaires and qualitative data with interview guidelines. Quantitative data analysis with computer programs. Descriptive analysis to see the distribution of variable frequencies and bivariate analysis to see the relationship between parenting and the risk of drug abuse. The test used was the Chi-Square test. As for qualitative data, theme analysis is used to obtain an overview of the object being studied. The results of the study stated that there was a relationship between parenting style and the risk of drug abuse in adolescents with a value of p = 0.015 (p<0.05). The result of qualitative research form the six informants support the hypothesis. Conclusion: parenting style have a meaningful relationship with the risk of drug abuse in adolescents and the qualitative data also explained the same thing. Factors that caused adolescent to use the drug were the absence of togetherness in the family and infrequent communication with his parents. That means the qualitative data support the hypothesis result.